Pengambilan Keputusan Petani dalam Program Peremajaan (Replanting) Kelapa Sawit di Kabupaten Sanggau - Altina, Nanda; Kusrini, Novira; Suharyani, Anita (Universitas Galuh, 2025)
The purpose of this study is to determine the factors that influence farmers' decision making in the oil palm replanting program. The research method is sequential mixed methods, especially the sequential explanatory strategy because it focuses on quantitative data and qualitative data as supporting data. The determination of the research site was done purposively (purposive methods). The selected area is Parindu Sub-district with consideration of the research location of Parindu Sub-district as the largest center of oil palm in Sanggau District. Based on the results of the study, the decision-making factors of farmers in replanting include experience (X3), land size (X5), capital (X8), which have a significant effect on farmers' decision-making in the replanting program. These factors have a significant impact on farmers' decision making.